Analisis Pengaruh Inflasi dan Harga Sukuk Ritel SR-008 terhadap Permintaan Sukuk Ritel SR-008 - Ahmad Fauzi (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2019)
This study aims to analyze the effect of the inflation rate and price of Sukuk Negara Ritel SR-008 on the level of demand of Sukuk Negara Ritel SR-008. This study uses data of market price and monthly sales volume of SR-008 during the period March 2015 to December 2017 with multiple linear regression analysis tool. The result shows that the variable of the inflation rate and price of SR-008 had an insignificantly negative effect on the level of demand for SR-008.